Integrasi Antara Komisi Pengawas Persaingan Usaha Dan Penyidik Kepolisian Dalam Penegakan Hukum Persaingan Usaha - Sukarmi Sukarmi (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The handling of unfair business competition cases by the Business Competition Supervisory Commission (KPPU) cannot run alone without the help and support of other law enforcement agencies, one of which is the Police Investigator. Its support is related to the summoning of the reported, witnesses and expert witnesses, collection of evidence and examinations that contain elements of competition law crimes as mandated by Law Number 5 of 1999. The issues examined in this research are, first, what is the role played by police investigators. in the enforcement of business competition law, has it been integrated with KPPU? second, how is the integration between KPPU and police investigators in enforcing business competition law? This is a normative legal research with a statutory approach and a case approach. The results of the study conclude that the role of Police Investigators in enforcing business competition law begins during the investigation and examination process. KPPU requests assistance to present the reported, witnesses, expert witnesses as well as anyone involved in business competition cases. Then after a decision is issued by the KPPU that has not been filed for objection, the investigator can follow up if it contains a criminal aspect. The integration between the KPPU and the Police Investigators of the Republic of Indonesia is manifested in the form of a Memorandum of Understanding which is then followed up with a cooperation to form a Working Group between KPPU and Police Investigators in handling business competition cases.